1978
DOI: 10.3758/bf03197443
|View full text |Cite
|
Sign up to set email alerts
|

Imagery and organization in memory: Instructional effects

Abstract: This paper concerns the relation between mental organization and memory performance. In a series of experiments, it is determined that interactive imagery exceeds separate imagery in cued recall and the organization of free recall. However, the two are indistinguishable in either recognition or the level of free recall unless some additional interunit organization is initially encoded. Although interactive imagery allows a list to be retained as fewer traces than does separate imagery, those traces are necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
4
47
1
Order By: Relevance
“…Subjects who employed separation imagery showed no increase in associative recall compared to a verbal repetition control, while an interactive image group showed a much higher level of performance. Begg (1973Begg ( , 1978 and Robbins, Bray, Irvin, and Wise (1974) found a similar outcome with concrete words, as did Neisser and Kerr (1973) when the words were embedded in sentences describing either interactive or separate pictorial frames. The research reported here shows that the mnemonic effects of separation imagery are intertwined with the imagined context in which the images of the word referents are set.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Subjects who employed separation imagery showed no increase in associative recall compared to a verbal repetition control, while an interactive image group showed a much higher level of performance. Begg (1973Begg ( , 1978 and Robbins, Bray, Irvin, and Wise (1974) found a similar outcome with concrete words, as did Neisser and Kerr (1973) when the words were embedded in sentences describing either interactive or separate pictorial frames. The research reported here shows that the mnemonic effects of separation imagery are intertwined with the imagined context in which the images of the word referents are set.…”
mentioning
confidence: 53%
“…Bower (1970Bower ( , 1972 interprets the superior performance he obtained with interactive imagery along much the same lines, saying, "I am convinced that associating meaningful terms is largely a matter of relating them in some organization" (1972, p. 86), a thesis that, he points out, has been advocated by Gestalt thinkers such as Asch (1969). Begg (1973Begg ( , 1978 has offered a sirnilar interpretation.…”
Section: General Dlscussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By the present account, successful performance requires that the cue be encoded, that the encoded cue contact or access its parent trace, and that the trace contain or provide sufficient data to allow response production (cf. Begg, 1978;Martin, 1967). Recall could fail because a cue contacts the wrong trace or none at all, or because a contacted trace leads to production of the wrong response or none at all.…”
mentioning
confidence: 99%
“…We chose the six procedures from prior research that claimed or seemed to claim that the procedures induced relational or item-specific processing. The three relational procedures and their source were category sorting (Einstein & Hunt, 1980;Hunt & Einstein, 1981), narrative construction (Bower & Clark, 1969), and relational imagery (Begg, 1978;Bower, 1970;McGee, 1980;Schwartz & Humphreys, 1974). The item-specific procedures and their source were pleasantness rating (Einstein & Hunt, 1980;Hunt & Einstein, 1981;Packman & Battig, 1978;Toglia & Battig, 1978), familiarity rating (Packman & Battig, 1978;Toglia & Battig, 1978), and single imagery (Begg, 1978;Bower, 1970;McGee, 1980).…”
mentioning
confidence: 99%